2018
DOI: 10.1128/jvi.01565-17
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomics Survey of Junín Virus Interactions with Human Proteins Reveals Host Factors Required for Arenavirus Replication

Abstract: Arenaviruses are negative-strand, enveloped RNA viruses that cause significant human disease. In particular, Junín mammarenvirus (JUNV) is the etiologic agent of Argentine hemorrhagic fever. At present, little is known about the cellular proteins that the arenavirus matrix protein (Z) hijacks to accomplish its various functions, including driving the process of virus release. Further, there is a little knowledge regarding host proteins incorporated into arenavirus particles and their importance for virion func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 113 publications
3
26
0
Order By: Relevance
“…These findings underline the relevance of the hits identified in our screen. Consistent with this hypothesis, we also identified TSG101 and PDCD6IP (also known as ALIX), which are involved in intracellular vesicular trafficking and have already been identified as arenavirus Z partners by others [26,46]. Our Y2H screen also identified various proteins involved in protein processing, including the endogenous γ2 isoform of AP-1 (AP1G2), which has been shown to interact with both MOPV and LASV Z protein.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings underline the relevance of the hits identified in our screen. Consistent with this hypothesis, we also identified TSG101 and PDCD6IP (also known as ALIX), which are involved in intracellular vesicular trafficking and have already been identified as arenavirus Z partners by others [26,46]. Our Y2H screen also identified various proteins involved in protein processing, including the endogenous γ2 isoform of AP-1 (AP1G2), which has been shown to interact with both MOPV and LASV Z protein.…”
Section: Discussionsupporting
confidence: 84%
“…To date, lists of host-cell proteins associated with various arenavirus infections have been established, providing new bases to investigate the potential roles of such interactions during the course of infection. With the exception of one study, which focused on the proteins of cellular origin associated with the Z protein of JUNV, most reports have focused on the NP and L interactomes during JUNV and LCMV infection [44][45][46][47][48]. However, these reports were based on the expression of tagged viral proteins through transfection or infection with genetically modified viruses and the identification of associated host-cell partners after purification and mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, findings obtained from studies involving Z expression by itself may not accurately capture some Z interactions that take place during mammarenavirus natural infection. Recently, an interactome analysis for JUNV Z protein has been reported (45). A limited degree of overlap was observed between host proteins identified in virions released from infected cells and those in VLPs from cells, in which the Z protein was expressed alone, suggesting that the host proteins found in VLPs may include proteins that are not involved in facilitating production of infectious viral progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of the MCODE 2-related viral budding process was the most significant with the smallest p-value of 10 -21.7 , strongly implying the association of the candidate host proteins with viral budding through the endosomal sorting complex required for transport (ESCRT). (Nuss et al 2014); HSV: herpes simplex virus type 1 (Stegen et al 2013); KSHV: Kaposi's sarcoma-associated herpesvirus (Zhu et al 2005); HCV: hepatitis C virus (Lussignol et al 2016); VV: vaccinia virus (Krauss et al 2002); IBV: infection bronchitis virus (Kong et al 2010); JUNV: Junin virus (Ziegler et al 2018); SARS: severe acute respiratory syndrome (Neuman et al 2008).…”
Section: Analysis Of Virion-packaged Host Proteins Involved In Rabv Imentioning
confidence: 99%
“…Sensitive mass spectrometry enables the identification of host proteins incorporated into virions with high accuracy and sensitivity. So far, proteomic studies have been performed on a number of purified virus preparations, including DNA viruses (Stegen et al 2013;Alejo et al 2018) and a broad range of RNA viruses (Shaw et al 2008;Radhakrishnan et al 2010;Nuss et al 2014;Lussignol et al 2016;McKnight et al 2017;Ziegler et al 2018), as well as virus-like particles (Vera-Velasco et al 2018). These studies have revealed substantial host proteins incorporated into viral particles, with several highlighting the utility of proteomics in understanding the mechanisms of virus-host interaction and identification of the essential role of cellular proteins in viral assembly or morphogenesis.…”
Section: Introductionmentioning
confidence: 99%